2022
DOI: 10.1149/10701.6251ecst
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of the Design Studio in New Learning Spaces: Virtual Design Studio in Architecture Pedagogy

Abstract: Architectural education has come a long way since the first formal school of architecture, École des Beaux-Arts, was started at Paris, France in 1816. 21st century architecture is constantly evolving through changes in technology, and now in 2020-’21, COVID-19 pandemic has brought the concept of architectural education going online. Due to the forced disruption to the traditional pedagogical environment, a new pedagogical paradigm has been established through online theory and studio classes. This has brought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In developing countries, the impact of OAE has highlighted the importance of assessing students' and instructors' satisfaction with online education, particularly in developing country contexts [62]. The shift to online classes has posed specific challenges for AE, primarily due to its reliance on the social studio setting, which has been a significant challenge in the new normal of online education [63]. Furthermore, experiences from specific institutions, such as the Mehran University of Engineering and Technology in Pakistan, have shown that while theoretical classes can be effectively taught online, practical/studio work in architecture is more challenging to deliver in an online format [64].…”
Section: Research Background and The Literature Gapmentioning
confidence: 99%
“…In developing countries, the impact of OAE has highlighted the importance of assessing students' and instructors' satisfaction with online education, particularly in developing country contexts [62]. The shift to online classes has posed specific challenges for AE, primarily due to its reliance on the social studio setting, which has been a significant challenge in the new normal of online education [63]. Furthermore, experiences from specific institutions, such as the Mehran University of Engineering and Technology in Pakistan, have shown that while theoretical classes can be effectively taught online, practical/studio work in architecture is more challenging to deliver in an online format [64].…”
Section: Research Background and The Literature Gapmentioning
confidence: 99%
“…Published by Francis Academic Press, UK -38-construction [7]. Compared with traditional buildings, prestressed prefabricated buildings have the advantages of simple construction technology, low construction requirements and short construction time, and can reap more economic benefits for the construction industry [8].…”
Section: Introductionmentioning
confidence: 99%
“…Artists can communicate their works to more people through the internet and digital media, and also use digital replication technology in the virtual world to allow more people to experience their artistic works. Harry and Kumar [6] conducted a transformation in the spatial construction method of architectural art design. With the development of digital design tools, architects and designers can use virtual design studios for digital design and modeling.…”
Section: Introductionmentioning
confidence: 99%